2019
DOI: 10.30843/nzpp.2019.72.257
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of the plant-associated endophytic fungus <i>Lecanicillium muscarium </i>to diamondback moth larvae

Abstract: Plutella xylostella (diamondback moth) is a prominent pest of brassicas which is now resistant to most insecticides. Despite years of research, the range of available products used in biological control of diamondback moth is still somewhat limited. We isolated putative endophytic fungi from New Zealand cabbage plants to search for unique biological control agents of diamondback moth larvae. The larvae were fed leaf discs from commercially grown cabbage covered in spores from endophytic fungal isolates to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previous studies have shown variability in lepidopteran mortality after the ingestion of EPF-colonized plants. Some of these studies have reported high mortality values after the ingestion of colonized discs [ 25 , 31 , 32 ], but others have only shown a reduction in fitness [ 33 , 34 ]. In the current study, the fitness of S. littoralis larvae feeding on Metarhizium -colonized discs and adults emerging from pupae developing from surviving larvae was reduced in terms of food consumption and reproductive potential, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown variability in lepidopteran mortality after the ingestion of EPF-colonized plants. Some of these studies have reported high mortality values after the ingestion of colonized discs [ 25 , 31 , 32 ], but others have only shown a reduction in fitness [ 33 , 34 ]. In the current study, the fitness of S. littoralis larvae feeding on Metarhizium -colonized discs and adults emerging from pupae developing from surviving larvae was reduced in terms of food consumption and reproductive potential, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, A. muscarius ARSEF 5128 was isolated from a greenhouse whitefly in Littlehampton (UK) ( Hall, 1982 ), B. bassiana ARSEF 3097 from a boll weevil in the Rio Grande Valley (USA) ( Wright, 1996 ) and C. fumosorosea ARSEF 3682 from a mealy bug in a greenhouse in Apopka (USA) ( Vidal et al., 1998 ). All strains have been shown to colonize plants as an endophyte upon artificial inoculation in various crops, including sweet pepper ( Kuchár et al., 2019 ; Rondot and Reineke, 2019 ; Nicoletti and Becchimanzi, 2020 ; Doherty et al., 2021 ; Wilberts et al., 2022 ). The strains were acquired from the Agricultural Research Service Collection of Entomopathogenic Fungal Cultures (ARSEF; New York, USA), and were stored as agar plugs in glycerol at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that larvae and pupae had a prolonged developmental period, and both fecundity and survival rates were reduced. Previous studies have also reported the effectiveness of various EPFs, such as B. bassiana and M. anisopliae, in suppressing insect pests [14,52,[61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%